2014
DOI: 10.4161/15548627.2014.981787
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagy flux is associated with neuronal cell death after traumatic brain injury

Abstract: Keywords: autophagy, autophagy flux, lysosome, neuronal cell death, traumatic brain injury Abbreviations: ACTB, actin; b; AIF1/IBA1, allograft inflammatory factor 1; AIFM1, apoptosis-inducing factor, mitochondrion-associated, 1; APC, adenomatous polyposis coli; ATG12, autophagy-related 12; ATG5, autophagy-related 5; ATG7, autophagy-related 7; CAPS12, caspase 12; CASP3, caspase 3; CCI, controlled cortical impact; CD68, CD68 molecule; CSPG4, chondroitin sulfate proteoglycan 4; CTSD, cathepsin D; GFP, green fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
263
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(290 citation statements)
references
References 55 publications
23
263
2
1
Order By: Relevance
“…Sun and associates 23 demonstrate that administration of bone marrow stromal cells is able to significantly suppress TBIinduced autophagy activity. Sarkar and colleagues 24 concluded that the accumulation of autophagosomes after severe TBI was because of lysosomal dysfunction. Taken together these studies emphasize the importance of macroautophagy in the pathophysiology and management of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Sun and associates 23 demonstrate that administration of bone marrow stromal cells is able to significantly suppress TBIinduced autophagy activity. Sarkar and colleagues 24 concluded that the accumulation of autophagosomes after severe TBI was because of lysosomal dysfunction. Taken together these studies emphasize the importance of macroautophagy in the pathophysiology and management of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in traumatic brain injury model, it was found that markers of increased and blocked autophagic flux co-localize with activated caspase-3. These results suggest that autophagy blockade could lead to apoptosis [32]. …”
Section: Discussionmentioning
confidence: 99%
“…For each experiment, data from all images from one region in each mouse were summed up and used for final statistical analysis. 31,48 At least 1000-2000 cells were quantified per mouse per area per experiment.…”
Section: Immunohistochemistry Image Acquisition and Quantificationmentioning
confidence: 99%